Exploring the impact of visual function degradation on manual prehension movements in normal-sighted individuals - Pablo Sanz Diez; Sandra Gisbert; Annalisa Bosco; Augusto Arias; Patrizia Fattori; Siegfried Wahl (PLoS ONE, 2025)
Impairments of visual function abilities, such as visual acuity and contrast sensitivity, can negatively impact our ability to perform manual prehension tasks. Despite the clear link between visual input and motor output, there is still limited understanding of how visual function deficits affect hand motor behavior. This study aimed to explore the impact of different levels of visual function degradation, specifically in terms of visual acuity and contrast sensitivity, on the reach and grasp components of manual prehension. To this end, visual function degradation was induced in young participants with normal vision using five different densities of Bangerter occlusion foils. Participants were instructed to perform a natural and accurate reach-to-grasp task towards a cylindrical object with two different diameters (3.5 or 7 cm) and positioned at two distances (25 or 50 cm). The effects of visual function degradation, object size, and distance were evaluated by recording the position and trajectory of the right hand using an optoelectronic motion capture system. Three-dimensional kinematic analysis revealed that visual function degradation in normal-sighted individuals directly altered the reach and grasp components of prehension movements. These alterations included longer movement durations, lower velocity and acceleration profiles, slower deceleration phases, over-scaled hand grip apertures, and greater trajectory deviations. The effects were dependent on the level of visual degradation induced and the intrinsic (size) and extrinsic (distance) object properties. Reductions exceeding 70% in visual acuity and 55% in CS had the most pronounced impact on prehension components. However, subtle reductions greater than 30% in visual acuity and 15% in contrast sensitivity were sufficient to trigger compensatory mechanisms. These findings provide further understanding of how visual function degradation affects prehension movement strategies, highlighting the crucial relationship between visual feedback quality and object properties in the motor online control of the transport, manipulation and spatial components. Our results offer new insights into the implications of visual impairments on manual prehension movements.